Dental students' and staff perceptions of the impact of learning environment disruption on their learning and teaching experiences. (6th October 2017) - The, A. J. M.; Adam, L.; Meldrum, A.; Brunton, P.
Abstract: Introduction: This project is a qualitative investigation into student and staff experiences of the effect of a major building redevelopment on their Dental School learning and teaching environments. Currently, there is little research exploring the impact of disruptions to the learning environment on students' learning and staff teaching experiences. Method: Data were collected in 2016 using an online survey, semi‐structured interviews and focus groups with students and staff. Data were analysed using a general inductive approach. Results: Four broad themes emerged as follows: (i) students valued having a space for personal and collaborative work within the Dental School; (ii) both staff and students positioned staff contributions to learning experiences above the role of the physical learning environment; (iii) the majority of staff and students not feel that the physical environment limited their clinical training; and (iv) staff and students were able to adapt to the impact of building redevelopment through resilience and organisation. Discussion: Results of this research have informed the provision of collegial spaces at the School, both as the building redevelopment continues, and in planning for the completed building.